2021
DOI: 10.18573/mas.122
|View full text |Cite
|
Sign up to set email alerts
|

Mexican capoeira is not diasporic! – On glocalization, migration and the North-South divide

Abstract: capoeira, glocalization, diaspora, North-South divide, bodily capital bildende Erfahrungen This paper contributes to the understanding of martial arts globalization processes. It focuses on the development of capoeira in Mexico, which is presented as an example of glocalization. In contrast to the diasporic capoeira observed by Delamont and Stephens in the UK, capoeira in Mexico is characterized by the proliferation of local groups with classes taught by Mexican instructors, as well as by advanced cultural rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A given martial artist might drill punches at the beginning of a class, while later working on their footwork or swordplay at home or in a local park (as mentioned in the vignette above). Through our various studies on various fighting systems [4,5], we have observed that some martial artists devote their time to a lifestyle of practice-training with friends on the weekends, their classmates in the evenings, and on their own within their home or work environments. All of martial arts demand continuous practice of such skills in order to develop a recognized level to then be able to teach, and it is worth noting that martial arts teachers and instructors are almost exclusively active practitioners.…”
Section: Martial Artists As Practitioners and Scholarsmentioning
confidence: 99%
“…A given martial artist might drill punches at the beginning of a class, while later working on their footwork or swordplay at home or in a local park (as mentioned in the vignette above). Through our various studies on various fighting systems [4,5], we have observed that some martial artists devote their time to a lifestyle of practice-training with friends on the weekends, their classmates in the evenings, and on their own within their home or work environments. All of martial arts demand continuous practice of such skills in order to develop a recognized level to then be able to teach, and it is worth noting that martial arts teachers and instructors are almost exclusively active practitioners.…”
Section: Martial Artists As Practitioners and Scholarsmentioning
confidence: 99%
“…Variations depend on the country and its particular history. David Sebastián Contreras Islas (2021) points out the differences between capoeira groups in the United Kingdom and Mexico, arguing against the diasporic character of capoeira. Comparing the work by Sara Delamont, Neil Stephens, and Claudio Campos (2017) in the UK with his research in Mexico, Contreras Islas mentions that in Mexico, the economic context does not provide a platform for a constant influx of mestres .…”
Section: Hierarchical Disruptions In International Settingsmentioning
confidence: 99%
“…I'd rather give you a degree in capoeira that gives Longe do Mar legitimacy'. [Cigano, personal communication, 29 September 2020] By making Cigano a mestre, Mestre Acordeon wanted to protect an legitimize the innovations of Longe do Mar, which has a long history of generating original plastic, scenic and musical work inspired by capoeira [Contreras Islas 2021]. However, Cigano reflects how making him a mestre was also a way to put a limit on those innovations:…”
Section: Becoming a Mexican Mestrementioning
confidence: 99%
“…Following in the steps of Lauren Miller [2013;2016;with Marion 2018], this contribution analyses the strategies used by non-Brazilian capoeiristas to obtain what she calls the 'ultimate marker of authenticity ' [Miller 2016: 43]: the title of mestre. I hypothesise that such strategies change with the structure of the social field of capoeira in different regions of the globe -for example, between 'diasporic capoeira' [Delamont & Stephens 2008] in the Global North and 'glocalized capoeira' in Mexico [Contreras Islas 2021]. To that end, I analyze the life stories of Cigano and Rosita 1 -the first Mexican man and woman to become mestres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation